Academic and methodological aspect of training future social workers for professional activity with young families - Dovha, Myroslava (ScienceRise: Pedagogical Education, 2020)
In modern social conditions, the family is in a crisis phase of its existence due to the low economic development of society and requires necessary support and social and legal protection from the society and the state to overcome the recurrent problems. This also requires the help of qualified social workers, who must be professionally trained to provide assistance to various types of families in difficult life circumstances. Therefore, we have determined the expediency of vocational training of future social workers for working with young families at the current stage of Ukrainian society development concerning gaining solid knowledge and ability to possess practically and apply in the protection of client groups, that is young families, in our case. We have considered the concept of "social worker" and its role as a specialist in the social and pedagogical sphere, as well as some aspects of a social worker's work with young families, which is carried out by preparing young people for family life, stabilization of family relationships, solving problems, related to family education and social rehabilitation of a young family. Therefore, taking into account the transformational changes in family relations and changes in family values in young families at the present stage of the development of Ukrainian society, it is necessary to emphasize the proper professional training of future social workers to work with this category of families. Moreover, based on the considered educational programs and working curricula of higher educational institutions, specified in the paper, an academic and methodological complex of the special course "Fundamentals of the social and legal protection of young families" has been developed to improve the training of future social workers for working with young families. It is based on the training of social workers for solving complex life family problems and specialized problems in the process of acquiring the necessary theoretical and practical knowledge, abilities and skills in the provision of social and legal protection while studying at a higher education establishment. In particular, the concepts and theoretical foundations of social and legal protection, factors and its determinants, the process and procedure of social establishments to provide social and legal protection to young families, familiarization with social phenomena and documents and regulations on the provision of social and legal protection